2012
DOI: 10.1001/archfacial.2012.35
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Following V-Y Advancement Flap Reconstruction of Large Upper Lip Defects

Abstract: Objective To characterize revision surgery following V-Y subcutaneous tissue pedicle advancement flap repair of large upper lip skin defects. Methods Retrospective review of upper lip skin defects ≥3.0 cm2 that were reconstructed with a V-Y subcutaneous tissue pedicle advancement flap at an academic tertiary care center. Depth and area of the defect, as well as involvement of the vermilion and nasal ala, were recorded as independent variables. Revision techniques were analyzed to identify patterns. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…Six studies reported outcomes on V-Y advancement flaps with the number of patients ranging from 13 to 109 with a range of upper lip defect locations with and without the involvement of neighboring cosmetic unit borders. [9][10][11][12][13][14] There was a single study on ergotrid flaps for upper lateral lip defects, 15 unspecified rotational flaps for apical triangle defects, 16 melolabial rotational flaps for apical triangle defects, 17 Karapandzic flaps for lateral upper lip defects, 18 alar crescent flaps for central upper lip defects, 19 and propeller facial artery perforator flaps for lateral upper lip defects. 20 Overall, there was significant heterogeneity in the complications as well as functional and aesthetic outcomes reported.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported outcomes on V-Y advancement flaps with the number of patients ranging from 13 to 109 with a range of upper lip defect locations with and without the involvement of neighboring cosmetic unit borders. [9][10][11][12][13][14] There was a single study on ergotrid flaps for upper lateral lip defects, 15 unspecified rotational flaps for apical triangle defects, 16 melolabial rotational flaps for apical triangle defects, 17 Karapandzic flaps for lateral upper lip defects, 18 alar crescent flaps for central upper lip defects, 19 and propeller facial artery perforator flaps for lateral upper lip defects. 20 Overall, there was significant heterogeneity in the complications as well as functional and aesthetic outcomes reported.…”
Section: Resultsmentioning
confidence: 99%
“…The V-Y Advancement Flap 3 places scars along aesthetic borders, but can result in elevation of the red lip due to scar contracture. The Keystone Flap 4 would result in the raising of the upper lip and blunting of the oral commissure.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, it is preferable to reconstruct the defect with a local flap to facilitate a good color and texture match. The use of VY flaps, rotation flaps, Abbe flaps, and combinations thereof in lip reconstruction has been reported [3][4][5][6]. However, no reports have described a surgical technique to obtain positional symmetry of the angulus oris.…”
Section: Discussionmentioning
confidence: 99%